Optimalisasi Pengetahuan Health Security pada Masyarakat Pasca Pandemi - Dewi Siyamti; Eka Adimayanti (CV. Ulil Albab Corp, 2024)
Indonesia has weathered the COVID-19 pandemic. The conditions that occured have a tremendous impact on all aspects of society. Restrictions on social activities, social distancing, prohibition of going home, covid 1, 2 and booster vaccines, implementation of health protocols and adaptation to new habits are part of the national strategy to return to normal activities during the pandemic. Various efforts were made by government to prevent and break the chain of transmission of the disease, but over time new variants emerged and returned to the disease. Family as the smallest unit in society that has the most influence in efforts to implement health awareness and healthy behavior of all family members. The purpose of this community service activity is to optimize public knowledge about health security.